The equalizer [videorecording (DVD)] - Washington, Denzel, 1954-; Moretz, Chloë, 1997-; Csokas, Marton, 1966-; Harbour, David, 1975- (Sony Pictures Home Entertainment, 2014)
McCall, a man who believes he has put his mysterious past behind him and dedicated himself to beginning a new, quiet life. But when McCall meets Teri, a young girl under the control of ultra-violent Russian gangsters, he can't stand idly by; he has to help her. Armed with hidden skills that allow him to serve vengeance against anyone who would brutalize the helpless, McCall comes out of his self-imposed retirement and finds his desire for justice reawakened.